2012
DOI: 10.1159/000338782
|View full text |Cite
|
Sign up to set email alerts
|

Biological Subtypes and Survival Outcomes in Breast Cancer Patients with Brain Metastases (Study of the Anatolian Society of Medical Oncology)

Abstract: Background: The aim of this study is to determine the relationship between the survival outcomes and biological subtype in breast cancer patients with brain metastases. Methods: We retrospectively evaluated clinical data from 422 breast cancer patients with brain metastases between 2001 and 2011 from referral centers in Turkey. The study population was divided into four biological subtypes according to their hormone receptor status and HER2 expression. Results: Systemic treatment prolonged median overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Niwinska et al reported improvements in median survival from 3 to 14 months with the addition of systemic therapy in patients with luminal breast cancer [ 20 ]. A similar result was seen in another study where the median overall survival of patients with luminal breast cancer was improved from 7.1 to 14.3 months with chemotherapy [ 55 ].…”
Section: Systemic Therapiessupporting
confidence: 86%
“…Niwinska et al reported improvements in median survival from 3 to 14 months with the addition of systemic therapy in patients with luminal breast cancer [ 20 ]. A similar result was seen in another study where the median overall survival of patients with luminal breast cancer was improved from 7.1 to 14.3 months with chemotherapy [ 55 ].…”
Section: Systemic Therapiessupporting
confidence: 86%
“…In a retrospective study of over 135 patients with BM from LBC, 88.8 % of them received local therapy (WBRT, RS or SRT), 56.7 % chemotherapy (mostly with taxanes) and 30.6 % hormonal therapy (mostly with aromatase inhibitors). Systemic treatment (chemotherapy ± hormonal therapy ± target therapy) prolonged median OS (14.3 vs 7.1 months, p  = 0.03) [52]. These data have been recently confirmed in a prospective study including 420 patients: OS with systemic treatment after WBRT increased 9 months in LBC [33].…”
Section: Systemic Anticancer Treatment By Tumor Subtypesmentioning
confidence: 86%
“…Human epidermal growth factor receptor (HER)2-positive and triple-negative breast cancer (TNBC) patients also have a higher risk of BM compared with luminal cancer patients [ 4 , 5 ]. In HER2-positive and TNBC patients, incidences of BM as high as 30–40 % have been described (Table 1 ) [ 4 6 ].…”
Section: Epidemiology Incidence and Risk Factorsmentioning
confidence: 99%